Extent of lymph node dissection improves survival in prostate cancer patients treated with radical prostatectomy without lymph node invasion. Issue 6 (19th February 2018) - Preisser, Felix; Bandini, Marco; Marchioni, Michele; Nazzani, Sebastiano; Tian, Zhe; Pompe, Raisa S.; Fossati, Nicola; Briganti, Alberto; Saad, Fred; Shariat, Shahrokh F.; Heinzer, Hans; Huland, Hartwig; et al.
Abstract : Purpose: To assess the effect of pelvic lymph node dissection (PLND) extent on cancer‐specific mortality (CSM) in prostate cancer (PCa) patients without lymph node invasion (LNI) treated with radical prostatectomy (RP). Methods: Within the Surveillance, Epidemiology, and End results (SEER) database (2004–2014), we identified patients with D'Amico intermediate‐ or high‐risk characteristics who underwent RP with PLND, without evidence of LNI. First, multivariable logistic regression models tested for predictors of more extensive PLND, defined as removed lymph node count (NRN) ≥75th percentile. Second, Kaplan‐Meier analyses and multivariable Cox regression models tested the effect of NRN ≥75th percentile on CSM. Finally, survival analyses were repeated using continuously coded NRN. Results: In 28 147 RP and PLND patients without LNI, 67.3% versus 32.7% exhibited D'Amico intermediate‐ or high‐risk characteristics. The median NRN was 6 (IQR 3‐10), the 75th percentile defined patients with NRN ≥11. Patients with NRN ≥11 had higher rate of cT2/3 stage (29.8 vs 26.1%), GS ≥8 (25.7 vs 22.4%), and respectively more frequently exhibited D'Amico high‐risk characteristics (34.6 vs 32.1%). In multivariable logistic regression models predicting the probability of more extensive PLND (NRN ≥11), higher biopsy GS, higher cT stage, higher PSA, more recent year of diagnosis, and younger age at diagnosis represented independent predictors. At 72 months after RP, CSM‐free rates were 99.5 versus 98.1% for NRN ≥11 and NRN ≤10, respectively and resulted in a HR of 0.50 ( P  = 0.01), after adjustment for all covariates. Similarly, continuously coded NRN achieved independent predictor status (HR: 0.955, P  = 0.01), where each additional removed lymph node reduced CSM risk by 4.5%. Conclusion: More extensive PLND at RP provides improved staging information and consequently is associated with lower CSM in D'Amico intermediate‐ and high‐risk PCa patients without evidence of LNI. Hence, more extensive PLND should be recommended in such individuals.